Clinical outcomes of overlapping versus non‐overlapping everolimus‐eluting absorb bioresorbable vascular scaffolds: An analysis from the multicentre prospective RAI registry (ClinicalTrials.gov identifier: NCT02298413). Issue 1 (13th May 2017) - Tarantini, Giuseppe; Mojoli, Marco; Masiero, Giulia; Cortese, Bernardo; Loi, Bruno; Varricchio, Attilio; Gabrielli, Gabriele; Durante, Alessandro; Pasquetto, Giampaolo; Calabrò, Paolo; Gistri, Roberto; Tumminello, Gabriele; et al.
Abstract : Objectives: To compare clinical outcomes of patients treated with overlapping versus non‐overlapping Absorb BVS.Background : Limited data are available on the clinical impact of stent overlap with the Absorb BVS bioresorbable stent.Methods : We compared outcomes of patients receiving overlapping or non‐overlapping Absorb BVS in the multicenter prospective RAI Registry.Results : Out of 1, 505 consecutive patients treated with Absorb BVS, 1, 384 were eligible for this analysis. Of these, 377 (27%) were in the overlap group, and 1, 007 (73%) in the non‐overlap group. The most frequent overlap configuration was the marker‐to‐marker type (48%), followed by marker‐over‐marker (46%) and marker‐inside‐marker (6%) types. Patients of the overlap group had higher prevalence of multivessel disease and higher SYNTAX score, and required more frequently the use of intravascular imaging. At a median follow‐up of 368 days, no difference was observed between overlap and non‐overlap groups in terms of a device‐related composite endpoint (cardiac death, TV‐MI, ID‐TLR) (5.8% vs. 4.1%, P = 0.20) or of a patient‐related composite endpoint (any death, any MI, any revascularization) (15.4% vs. 12.5%, P = 0.18). Cardiac death (1.0% vs. 1.3%, P = 0.54), MI (4.5% vs. 3.6%, P = 0.51), TVR (4.5% vs. 3.6%, P = 0.51) and stent thrombosis (1.1 vs. 1.5%, P = 1.00) were also comparable between groups. When assessing outcomes of the overlap population according to overlap configurations used, no difference was observed in terms of the device‐ or patient‐related composite endpoints.Conclusions : Outcomes of patients with or without overlapping BVS were comparable at mid‐term follow‐up despite higher angiographic complexity of the overlap subset. © 2017 Wiley Periodicals, Inc.